Relationships between psychological, clinical aspects and eating behavior in individuals with diabetes: cross-sectional study - Kacar, Mihrican; Yangilar, Filiz; Karahan Yilmaz, Sevil; Yilmaz, Nazife (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: Eating disorders are closely related to mental status, and individuals with diabetes have a significantly increased risk of developing an eating disorder. Objective: This study aims to evaluate the possible association of cognitive restriction, uncontrolled eating, emotional eating factors, and eating disorders with depression in individuals with diabetes. Methods: A cross-sectional study was carried out on 132 patients who were diagnosed with diabetes. The Beck Depression Inventory (BDI) was used to assess the depression status of individuals, the Three-Factor Eating Questionnaire (TFEQ-R18) to measure eating habits, and the Night Eating Questionnaire (NEQ) to obtain information about night eating behavior. All anthropometric measurements were taken by the researcher. Results: It was determined that there was a ’mild depression’ state in both the Type 1 diabetes patient group (14.10±8.26) and the Type 2 diabetes patient group (14.74±7.64). A linear, moderate, and significant correlation was found between BDI scores and NEQ scores in individuals with type 1 diabetes (r=0.547, p<0.001). In individuals with type 2 diabetes, an inverse, moderate, and significant correlation was found between BDI scores and cognitive restriction scores (r=-0.406, p=0.029). For the individuals in the two groups, statistically significant differences were found in the scores obtained from the BDI, NEQ, and TFEQ-R18 in terms of the history of mental illness and obesity, diabetic diet, and hypoglycemia (p<0.05). Conclusions: In this study, it has been shown that the effect of mental illness and obesity history on current eating behavior may be on night eating behavior, cognitive restriction, and uncontrolled eating. It is likely that compliance with the diabetic diet and prevention of hypoglycemia will be reflected in eating behavior and anthropometric measurements.